Role of Inflammasomes in Liver Disease and Autoimmune Hepatitis vs. Infectious Hepatitis: An Extensive Review - Gadour, Eyad; Miutescu, Dr. Bogdan (International Journal of Innovative Research in Medical Science, 2023)
Autoimmune hepatitis (AIH) is a chronic inflammatory condition characterized by periportal inflammation, increased immunoglobulins and autoantibodies, and a significant response to immunosuppression. In genetically predisposed people, an environmental contaminant is thought to induce an immune-mediated attack against liver antigens. A wide range of clinical manifestations, from chronic indolent illness to fulminant hepatic failure, can be detected, and the diagnosis necessitates the exclusion of other causes of liver disease. Corticosteroid therapy must be started early and tailored to the person. The variety of clinical symptoms, uncertainty regarding the natural history, developing notions about therapeutic end targets, and the existence of many alternative immunosuppressive drugs can confound therapeutic decisions. The ultimate aim of the desired therapy is to achieve normal liver tests and tissue; however, this must be balanced against the danger of side effects. Early liver transplantation may be beneficial for decompensated patients. When therapy is started quickly and aggressively, the long-term prognosis is excellent. Our article addresses AIH and provides a thorough overview of its clinical presentation, risk factors, immunopathogenesis, modern diagnostic criteria, recent advancements in therapy, a brief discussion of AIH during pregnancy, and long-term effects on cirrhosis and hepatocellular carcinoma in patients with AIH.